Tropospheric ozone and aerosols measured by airborne lidar during the 1988 Arctic boundary layer experiment - Butler, Carolyn F.; Kooi, Susan A.; Browell, Edward V. (1991)
Ozone (O3) and aerosol distributions were measured from an aircraft using a differential absorption lidar (DIAL) system as part of the 1988 NASA Global Tropospheric Experiment - Arctic Boundary Layer Experiment (ABLE-3A) to study the sources and sinks of gases and aerosols over the tundra regions of Alaska during the summer. The tropospheric O3 budget over the Arctic was found to be strongly influenced by stratospheric intrusions. Regions of low aerosol scattering and enhanced O3 mixing ratios were usually correlated with descending air from the upper troposphere or lower stratosphere. Several cases of continental polar air masses were examined during the experiment. The aerosol scattering associated with these air masses was very low, and the atmospheric distribution of aerosols was quite homogeneous for those air masses that had been transported over the ice for greater than or = 3 days. The transition in O3 and aerosol distributions from tundra to marine conditions was examined several times. The aerosol data clearly show an abrupt change in aerosol scattering properties within the mixed layer from lower values over the tundra to generally higher values over the water. The distinct differences in the heights of the mixed layers in the two regions was also readily apparent. Several cases of enhanced O3 were observed during ABLE-3 in conjunction with enhanced aerosol scattering in layers in the free atmosphere. Examples are presented of the large scale variations of O3 and aerosols observed with the airborne lidar system from near the surface to above the tropopause over the Arctic during ABLE-3.